After the Publication of R.Orlova's Article «Dramaturgy of Saroyan». - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
Many works of William Saroyan are translated into Russian nowadays, presented in numerous editions, interpreted by many literary critics. This paper deals with the peculiarity of the first-stage acquaintance with Saroyan in Russian. The author throws light on the very important role of Raisa Orlova – an authority in the knowledge of American literature – in that long-standing process. The attention is given as well to some R.Orlova's personal contacts with Armenia and armenians.
Keywords: W.Saroyan, R.Orlova, editions, introdaction, afterword, armenian motive